Software Defined Network For Smart Hom - Murtadha, Shujairi (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2021)
As the world embraces Smart Home Technologies, there is a need for an efficient managementplatform for these services. Accordingly, this article proposes the Software-Defined SmartHome (SDSH) platform, which offers openness, virtualization, and centralization. The platform canintegrate heterogeneous devices and offer flexibility between user demands and family scenes. Thisarticle offers a detailed explanation of SDSH and using it as a Firewall, explores potential applications,and identifies challenges and opportunities associated with its adoption.
Keywords: SDN; Smart Home; SDSH; IoT; Raspberry Pi